2021
DOI: 10.1038/s41419-021-04330-2
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc-activated USP2-AS1 suppresses senescence and promotes tumor progression via stabilization of E2F1 mRNA

Abstract: The c-Myc oncoprotein plays a prominent role in cancer initiation, progression, and maintenance. Long noncoding RNAs (lncRNAs) are recently emerging as critical regulators of the c-Myc signaling pathway. Here, we report the lncRNA USP2-AS1 as a direct transcriptional target of c-Myc. Functionally, USP2-AS1 inhibits cellular senescence and acts as an oncogenic molecule by inducing E2F1 expression. Mechanistically, USP2-AS1 associates with the RNA-binding protein G3BP1 and facilitates the interaction of G3BP1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 73 publications
2
10
0
Order By: Relevance
“…These results suggested that USP2-AS1 might be a hypoxia-regulated oncogenic lncRNA during HNSCC progression. Previously, USP2-AS1 has been reported as a direct target of MYC [ 27 ]. In this study, we knocked down MYC in the HNSCC cell line FaDu and found that USP2-AS1 levels were also decreased upon MYC depletion ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggested that USP2-AS1 might be a hypoxia-regulated oncogenic lncRNA during HNSCC progression. Previously, USP2-AS1 has been reported as a direct target of MYC [ 27 ]. In this study, we knocked down MYC in the HNSCC cell line FaDu and found that USP2-AS1 levels were also decreased upon MYC depletion ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Xiang et al reported 14 hypoxia-regulated lncRNA signatures that could be used for prognosis prediction [ 38 ]. USP2-AS1 has been reported to be possibly regulated by MYC [ 27 ]. As a global transcription factor, MYC regulates the expression of a wide range of genes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the density ratio between pRb and Rb was not parallel to the E2F1 protein level, indicating that there might be other Rb-independent mechanisms for the regulation of E2F1. In fact, Li et al [ 32 ] have reported that MYC stabilizes the mRNA of E2F1 by activating the lncRNA USP2-AS1, thereby increasing the level of E2F1. Hence, the elevated MYC level by HBx-T81P/S101P/L123S ( Figure 3 D and E) might also be involved in the regulation of E2F1 levels.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding what factors might be preventing or reversing senescence might help to identify therapeutic targets to prevent melanomagenesis. Recent studies have shown the effects of c-Myc-activated USP-AS1 [ 43 ] and ZNF [ 43 ] in bypassing senescence and promoting tumorigenesis. Thus, it would be interesting to evaluate whether keratinocytes enable the secretion of these factors in the presence of oncogenic melanocytes and/or by themselves.…”
Section: Discussionmentioning
confidence: 99%